Effect of soybean (Glycine max) intercropping under different nitrogen levels on yield, yield attributes and quality of maize (Zea mays) - KUSHWAHA, H S; CHANDEL, A S (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during rainy season of 1992 and 1993 to study the effect of N application on yeild,yield attributes and quality of maize (Zea mays L.) in soybean [Glycine max (L.) Merr.] + maize intercropping system. The treatment consisted of 4 levels of nitro gen (0, 50, 100, 150 kg N/ha) for soybean + maize intercropping system and 0 and 120 kg N/ha for sale crop of maize. Cob number, cob length, number of grains/cob, 1 000-grain weight, grain yield, stover yield and protein yield of maize increased significantly under intercropping system. Maximum number of cobs were recorded in soybean + maize at 150Â Â  kg N/ha during both the years. Maximum cob length was recorded in maize pure at 120 kg N/ha during both the years. The application of 100 kg N/ha in soybean + maize system showed the bighest number of grains/cob and 1000-grain weight of maize among maize pure and maize + soybean systems. The maximum grain yield (2 654 and 3 606 kg/ha) of maize was recorded with 100 kg N/ha to soybean + maize intercropping system, which was significantly higber than soybean + maize at 0 and 50 kg N/ha and maize pure at 0 kg N/ha during both the years. Maize-equivalent grain yield (3729 and 4 412 kg/ha) was maximum in soybean + maize at 100 kg N/ha. Protein content of maize grain improved withN application in maize + soybean system. Maximum protein yield (303 and 389 kg/ ha) of maize grain was recorded in soybean + maize at 100 kg N/ha treatment.